2005
DOI: 10.1002/mnfr.200500003
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity and metabolism oftrans-resveratrol orally administered to Wistar rats

Abstract: The purpose of this study was to investigate the implications of selected chemopreventive parameters and metabolic conversion of resveratrol in vivo. In two 8-week long feeding experiments with rats, a low-resveratrol diet containing 50 mg resveratrol per kg body weight (bw) and day and a high-resveratrol diet with 300 mg per kg bw and day were administered. For chemopreventive evaluation selected phase I and phase II enzymes of the biotransformation system, the total antioxidant activity, and the vitamin E st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
183
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(198 citation statements)
references
References 34 publications
(44 reference statements)
14
183
1
Order By: Relevance
“…No significant differences between Groups were recorded. This result is consistent with the literature in showing that oral administration of resveratrol is not harmful at the dosage and for the period administered [12,13,32] .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…No significant differences between Groups were recorded. This result is consistent with the literature in showing that oral administration of resveratrol is not harmful at the dosage and for the period administered [12,13,32] .…”
Section: Discussionsupporting
confidence: 93%
“…It modulates lipid and lipoprotein metabolism and is a potent chemopreventive agent. It also has antioxidant and anti-inflammatory properties [12,13] . Seidman et al [17,18] demonstrated the effectiveness of resveratrol against noise-induced hearing loss in two studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the modifications just mentioned have been long recognized and studied for representative members of this huge family of natural compounds, including resveratrol, which is of specific interest here. Rapid glucuronidation and sulfation in enterocytes, hepatocytes, and other cells (e.g., [14][15][16][17][18][19][20][21]) and re-export to the intestinal lumen by MDR proteins [15,22,23], or possibly OATPs [24], are thought to limit the potential impact of this celebrated "natural drug" in vivo. This is a pity, given the pleiotropic effects this dietary compound is reported to have in important pathophysiological respects (for recent reviews see, e.g., [25][26][27][28][29][30]).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, interest in the combinatory effect of different phytochemicals is growing, with respect to the multi-targeted action of numerous components of a food matrix. Wenzel and co-workers found that metabolism of resveratrol present in beverages such as wine or grape juice is inhibited by other polyphenols due to competitive reactions with Phase -II enzymes, resulting in an increased concentration of the free form (Wenzel et al, 2005). It is suggested that an efficient chemoprevention strategy lies in the use of combinations of several chemopreventive and/or therapeutic agents which may exert multi-targeted action.…”
Section: Resultsmentioning
confidence: 99%